The adoption of asynchronous online courses by professors at Memorial University of Newfoundland: A case study - Reid, Scott (University of Ottawa (Canada), 2008)
This study examined the experiences of university professors at one university as they adopted and used online courses. It drew on various theories of change to analyze the adoption of online courses by professors. Qualitative methods, involving semi-structured interviews with 32 university professors, were used to gather information about the various factors influencing university professors' adoption of online courses. Three levels of analysis---societal, institutional, and individual---were used to organize the qualitative data. The findings provide insight into the adoption experiences of professors at this university and also the future development of this new technology for teaching. These insights expand understanding of this new teaching medium for professors, university administrators, and researchers undertaking work in this area. Avenues for further research are also identified.
Keywords: Education, Technology of.; Education, Higher.